Correlation of ultrasound measured testicular volume with waist circumference, hip circumference, waist-hip ratio and conicity index in Nigerian adults - A L Asomugha; C I Madubogwu; N U Madubogwu; M E Aronu (Nigerian Journal of Medicine, 2018)
Background: Accurate testicular volume measurement is one way to assess testicular function. Some obese males exhibit altered levels of circulating sex steroids; decreased levels of total testosterone (T) and sex hormone binding globulin (SHBG) and increased estrogens levels. Some anthropometric measurements are markers for obesity. Objective: This study aims to evaluate the correlation of testicular volume measured by ultrasound with some anthropometric measurements: Waist circumference, Hip circumference, Waist-Hip Ratio (WHR), and Conicity Index in adult males. Methodology: One hundred and twenty-five adult male subjects comprising staff and students of a University Teaching Hospital, were recruited. The subjects' height, weight, waist circumference and hip circumference were measured and used to calculate the WHR and Conicity Index. Ultrasound measurement of the length, width and height of both testes were done and used to calculate the volumes. Results: The age of the subjects ranged from 19 to 29 years with a mean of 23.48±2.26. The mean ultrasound testicular volumes for the right and left testes were: 15.38±3.29ml and 15.29±3.89ml using the first formula; 22.86±5.43ml and 23.54±6.88ml for second formula; 21.20±5.28ml and 20.87±5.35ml for the third formula respectively. The calculated mean for height, weight, Waist circumference, Hip circumference, WHR and Conicity Index were: 174.64±6.36cm, 68.68±8.25kg, 77.51±5.44cm, 88.76±4.46cm, 0.87±0.40 and 1.14±0.05 respectively. The left, right and combined testicular volumes showed weak negative correlation with the Waist circumference, Hip circumference, WHR and Conicity Index. Conclusion: Ultrasound measured testicular volume showed weak negative correlation with the Waist circumference, Hip circumference, WHR and Conicity Index in Nigerian adults.